Productivity improvement in industry by using witnes software - Wan Faizul, Wan Mustafa (2008)
Productivity is a method to measure the performance or efficiency in the industry, organization or factory. The project is focused on trim line production of Mercedes Benz car. The study are about to improve production productivity, reduce waiting time in production line, increase the production in one day in order to achieve the target, used up all the space in the factory usefully and increase the busy at production line to the maximum by using Witness software. Person in charge and workers interview is done to collect some information about the assembly line in determining problems occur. Other than that, direct observation method, archival data and self collecting data are used. Live experiments are conducted on production lines. Four problems are identified such as reworked, not enough manpower, delayed process, high waiting time, and low production which are not in the target for one day production. Interventions are made to rectify the problems such as to reduce waiting time in problem’s section by adding buffer which for temporarily storage for finished part in order to minimize waiting time for finished section sent the finish part without have to wait. As a result, the production productivity for the trim line production is increased.